A rare case of primary cutaneous diffuse large B-cell lymphoma, leg type in a patient with chronic lymphedema of the leg - Basavaraj Vijaya; Saravu RamaBhatta Narahari; Mysore Krishna Shruthi; Guruprasad Aggithaaya (Wolters Kluwer Medknow Publications, 2019)
A rare complication of chronic lymphedema is development of cutaneous malignant tumors particularly cutaneous lymphomas. We report a case of primary cutaneous diffuse large B-cell lymphoma, leg type, associated with chronic lymphedema of the lower limbs. A literature review identified 12 additional cases of primary cutaneous lymphomas associated with chronic lymphedema. Chronic lymphatic stasis may cause a local dysfunction of the immune system that predisposes to the induction of neoplasia, cutaneous lymphomas in particular.